Investigation of dispersion characteristic in tapered fiber - Harun, Sulaiman Wadi; Lim, Kok Sing; Ahmad, Harith (IOP Publishing, 2011)
A dispersion characteristic of a tapered fiber is investigated using temporal interferometer by employing a broadband amplified spontaneous emission (ASE) source to generate an interference pattern. The dispersion characteristic of the tapered fiber is acquired from a Fourier transform of the interference pattern. The second and third order dispersions of β2 and β3 are obtained at 1544.1 nm for -600 ps2/km and -2 ps3/km, respectively. The β2 value obtained is observed to be more than 300 times higher than that of a non-tapered single mode fiber. The high dispersion characteristic is due to tapering process that changes the birefringence characteristic due to the reduction in the fiber's size and structure.